The bacteriological assessment of urine in patients with premature rupture of membranes - Tanshen, Kumer; Goshwami, Panchami; Tribedi, Shanta; Haider, Sarvin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: PROM occurs in 10% of all pregnancies. Urinary tract infections (UTIs) are the most common bacterial infections in pregnancy. Asymptomatic bacteriuria (ASB), occurring in 2-11% of pregnancies, is a significant predisposition to the development of pyelonephritis and UTI, which are associated with obstetrical complications, such as preterm labor and low birth weight infants. Methods: This study was carried out at the Department of Obstetrics and Gynaecology, Mymensingh Medical College Hospital, Mymensingh, Bangladesh, over a period of 6 Months from July 2011 to December 2011. Results: A total of 100 patients of PROM were included in this study within this period. The mean age was 27.10±4.49 (SD) years in patients’ of PROM, and the prevalence of gestational week was found at 26 (26%) at 30 weeks, 20 (20%) at 32 weeks, 22 (22%) at 33 weeks, 28 (28%) were at 34 weeks, and 4 (4%) were at 39 weeks. Most of the cases were no growth (84%), E. coli (12%), Streptococcus (2%), Candida (1%), and anaerobs (1%). 52% were preterm, and 42% were term delivery. 40% developed chorioamnionitis, 10% developed puerperal sepsis, and 8% developed DIC, and this prospective observational study revealed that 16% of cases of PROM patients’ were associated with urinary tract infection. Conclusions: This study was undertaken to determine the bacteriological assessment of urine of patient’s with premature rupture of membrane. It is found that 16% of patients’ with PROM have urinary tract infection with E. coli, Group B streptococcus, anaerobs, and candida organisms.